FRAGMENTATION AND DEGRADATION OF THE URBAN LANDSCAPE IN HERGLA, TUNISIA - Chaggar, Meriem; Boubaker, Mohsen (International Journal of Engineering Technologies and Management Research, 2018)
This research proposes to identify the factors of the urban landscapes degradation in Hergla’s city (Tunisia) according on the citizen participation. It is based on the survey method which is developed around two axes: the citizen perception of urban landscapes and the factors of their degradation. According to the responses obtained, "the sea" represents the particular value of the landscapes identified as "quality" in Hergla. Citizens don’t appreciate landscapes of urban sprawl which makes the city lose its identity. Moreover, the lack of citizen participation in the urban actions and the non-observance of the urban regulations are the most cited factors of the landscape degradation. These results highlight the importance of involving the citizens in the planning process for a sustainable territory.